2009
DOI: 10.1111/j.1556-4029.2009.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Explosive Particles in Fingerprints Using Attenuated Total Reflection‐Fourier Transform Infrared Spectromicroscopy

Abstract: The application of attenuated total reflection (ATR)-Fourier transform infrared (FTIR) spectromicroscopy for detection of explosive particles in fingerprints is described. The combined functions of ATR-FTIR spectromicroscopy are visual searching of particles in fingerprints and measuring the FTIR spectra of the particles. These functions make it possible to directly identify whether a suspect has handled explosives from the fingerprints alone. Particles in explosive contaminated fingerprints are either ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 15 publications
(33 reference statements)
0
38
0
3
Order By: Relevance
“…The characteristic spectral patterns associated with both DART and SALDI-systems can be used identify these explosives with good sensitivity and use of MS-MS via collision induced dissociation (CID) can add further un-ambiguous evidence for their identity. In contrast screens for explosives in fingermarks using IR/Raman spectroscopy [14,15] require further complex sample processing to obtain such MS identification. An example of the SALDI-MS-MS spectrum for PETN is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic spectral patterns associated with both DART and SALDI-systems can be used identify these explosives with good sensitivity and use of MS-MS via collision induced dissociation (CID) can add further un-ambiguous evidence for their identity. In contrast screens for explosives in fingermarks using IR/Raman spectroscopy [14,15] require further complex sample processing to obtain such MS identification. An example of the SALDI-MS-MS spectrum for PETN is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ATR-FTIR spectroscopy has also been used to detect other exogenous compounds such as components relating to explosives. In one particular study [34], trinitrotoluene (TNT), ammonium nitrate (AN), and trinitrobenzene (TNB) were successfully identified using ATR-FTIR spectroscopy. Another popular spectroscopic method is Raman spectroscopy.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…Bhargava et al have reported the use of reflection-absorption mode for the distinction of overlapping fingerprints based on differences in their chemical origins [60]. FTIR imaging has been used to detect exogenous trace residues associated with forensic evidence, e.g., explosives [60][61][62] and illegal substances [63].…”
Section: Vibrational Spectroscopic Imagingmentioning
confidence: 99%